Evaluation of CT angiography of the thoracic aorta with ECG gating in cases of dissection - Widiatmoko, Mahfud Edy; Supriyaningsih, Eny; Sutoro, Shinta Gunawati; Irsal, Muhammad; Anggraeni, Dewi (International Journal of Health Science and Technology, 2024)
Type A aortic dissection is a longitudinal tear separating the intima layer from the aortic media and is often not clearly visible due to cardiac motion which can reduce image quality and misrepresent the lumen so that the flowing blood causes several problems such as the aortic root and ascending aorta. CT angiography with ECG gating was chosen to reduce the images of cardiac movement. The purpose is to evaluate the examination procedure and anatomical description of the CT Angiography examination with Gating ECG. The research method is descriptive qualitative research with a case study approach with samples selected based on the examination diagnosis with type A aortic dissection. Observation, documentation, interviews did data collection. Data analysis is described in a descriptive narrative, and a conclusion is drawn. The result of the study is that CT angiography examination with ECG gating provides accurate information that the coronary arteries originate from the true lumen. In this phase, there are no lines that show a significant picture of heart movement disorders so that the coronary arteries can be assessed properly. The anatomical features of MIP, CPR, and VRT visualize the aortic root region until the coronary arteries are displayed more informatively than heart movement disorders. The conclusion is that CTA examination with ECG gating can show the aortic root in cases of type A dissection located at the root or ascending aorta and minimize heart movement interference with MIP, CPR and VRT.